Preparation method and application of nitrogen-rich carbon material loaded with Cu2O in situ
By loading Cu2O in situ on nitrogen-doped carbon materials, the problem of aggregation and instability of Cu2O catalysts during electrocatalytic carbon dioxide reduction is solved, and the effect of efficient conversion of CO2 to C2 products is achieved.
Patent Information
- Application Number
- CN202411860631.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-18
AI Technical Summary
Among the existing electrocatalytic carbon dioxide reduction catalysts, Cu2O catalysts are prone to aggregation and unstable during the reaction, resulting in unsatisfactory C2 selectivity and activity.
By loading Cu2O in situ on nitrogen-doped carbon materials, nitrogen-rich carbon materials are prepared by high-pressure hydrothermal reduction and carbonization processes, which increases the specific surface area and chemical stability of the catalyst, promotes the stable existence of Cu2O, and thus improves the catalytic performance.
This method significantly improves the activity and selectivity of the catalyst to reduce CO2 to C2+ products, and the Faraday efficiency is greater than 60% at high total current density, which has broad application value.
Smart Images

Figure CN119640307A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalytic carbon dioxide reduction materials, and in particular relates to a preparation method and application of a nitrogen-rich carbon material loaded with Cu2O in situ. Background Art
[0002] Electrochemical carbon dioxide reduction reaction (ECO2RR) is a method of converting carbon dioxide into high value-added products (CO, CH4, C2H4 and C2H5OH, etc.) using clean energy for storage. It is both practical and technically feasible and is considered to be an effective way to alleviate climate problems caused by excessive CO2 emissions. Among the various products of ECO2RR, carbon dioxide (C2) products (such as C2H4 and C2H5OH) have attracted great attention due to their high energy density, great value and wide application.
[0003] Among the numerous ECO2RR catalysts, Cu, as the only metal element that can convert CO2 into hydrocarbons, has been the subject of much research. Among Cu-based catalysts, Cu2O has a moderate coordination energy for *CO and *H intermediates, which enables CC coupling to produce C2H4 and C2H5OH. However, due to the Cu2O nanocatalyst in the ECO2RR process, the + Will be reduced to Cu 0 This causes the catalyst to easily aggregate and become unstable, resulting in unsatisfactory C2 selectivity and activity.
[0004] Based on the defects of catalysts in the current electrocatalytic carbon dioxide reduction system, it is necessary to improve it. Summary of the invention
[0005] In order to overcome the above problems, the present invention provides a method for preparing a nitrogen-rich carbon material loaded with Cu2O in situ and its application.
[0006] The invention adopts gelatin, glucose and copper salt dissolved in deionized water for high pressure hydrothermal reduction to obtain monovalent copper ion doped gelatin solution, and obtains nitrogen-rich carbon material loaded with Cu2O in situ after freeze drying, thermal crosslinking and high temperature carbonization treatment. Nitrogen-doped carbon is used as a substrate, and the advantages of carbon material such as large specific surface area, stable chemical properties and good electrical conductivity are brought into play. Nitrogen atom doping can induce more electrons to enter the carbon matrix, thereby generating more active sites. Stably existing Cu2O (111) can promote CO2 activation to generate CO* and CC coupling process, thereby generating multi-carbon products, and greatly improving the catalytic performance.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] A method for preparing a nitrogen-rich carbon material loaded with Cu2O in situ, characterized in that it comprises the following steps:
[0009] Step 1: Preparation of monovalent copper ion-doped gelatin precursor
[0010] 1.1 Add gelatin and anhydrous glucose into a solvent to swell and dissolve, thereby obtaining a solution of gelatin and glucose mixture;
[0011] 1.2 Then, add the copper salt to the mixed solution of gelatin and glucose obtained in step 1.1, and stir to obtain a mixture;
[0012] 1.3 The mixture obtained in step 1.2 is placed in a hydrothermal reactor for hydrothermal reaction to obtain a monovalent copper ion-doped gelatin solution;
[0013] 1.4 The monovalent copper ion-doped gelatin solution obtained in step 1.3 is placed in a refrigerator and frozen to obtain a monovalent copper ion-doped gelatin frozen solid;
[0014] 1.5 The monovalent copper ion-doped gelatin frozen solid obtained in step 1.4 is placed in a freeze dryer, and after drying, a monovalent copper ion-doped gelatin precursor is obtained;
[0015] Step 2: Preparation of in-situ Cu2O-loaded nitrogen-rich carbon materials for CO2 reduction
[0016] 2.1 The monovalent copper ion-doped gelatin precursor obtained in step 1 is placed in a muffle furnace for cross-linking reaction to obtain cross-linked monovalent copper ion-doped gelatin;
[0017] 2.2 The cross-linked monovalent copper ion-doped gelatin obtained in step 2.1 is carbonized under N2 or Ar conditions to obtain a nitrogen-rich carbon material in situ loaded with Cu2O for CO2 reduction.
[0018] Furthermore, in the step 1.1, the mass fraction of gelatin is 10%-20%, the mass fraction of anhydrous glucose is 1%-10%, the solvent is deionized water, the swelling temperature is 15-40°C, and the dissolution temperature is 40-60°C;
[0019] In the step 1.2, after the copper metal salt is added to the mixed solution of gelatin and glucose, the mass fraction of the copper metal salt is 1-5%; and the stirring time is 40-60 minutes.
[0020] Furthermore, in the step 1.3, the reaction temperature of the mixture in the hydrothermal reactor is 100-200° C. and the reaction time is 1-2 h;
[0021] In the step 1.4, the freezing temperature of the refrigerator is -80-0°C, and the freezing time is 3-8h;
[0022] In the step 1.5, the freeze-drying temperature in the freeze-drying method is -60 to -50°C, wherein the freeze-drying time is 20 to 24 hours;
[0023] Furthermore, in the step 2.1, the cross-linking temperature in the cross-linking method is 200-300°C, the cross-linking time is 1-3h, and the heating rate is 1-10°C / min.
[0024] Furthermore, in the step 2.2, the carbonization temperature in the carbonization method is 500-1000° C., and the carbonization time is 1-2 hours.
[0025] The invention also discloses a nitrogen-rich carbon material loaded with Cu2O in situ, which is characterized in that it is prepared according to the above-mentioned preparation method.
[0026] The present invention also discloses an application of the above-mentioned nitrogen-rich carbon material loaded with Cu2O in situ in the electroreduction of CO2:
[0027] The electrode material was prepared by in-situ loaded Cu2O nitrogen-rich carbon material for electrocatalytic CO2 reduction.
[0028] Furthermore, the application of the in-situ Cu2O-loaded nitrogen-rich carbon material in the electro-reduction of CO2 comprises the following steps:
[0029] The in-situ Cu2O-loaded nitrogen-rich carbon material is dispersed in a mixed solution of ethanol and naphthol film ethanol dispersion, and drop-coated on carbon paper as a working electrode, an Ag / AgCl electrode as a reference electrode, and a platinum sheet as a counter electrode; the cathode electrolyte is a CO2-saturated KOH solution.
[0030] Furthermore, the cathode electrolyte is one of 0.1-1M KOH solution, NaOH solution, and KHCO3 solution.
[0031] Furthermore, the loading amount of the in-situ Cu2O-loaded nitrogen-rich carbon material is 0.5-2 mg / cm 2 .
[0032] The nitrogen-rich carbon material loaded with Cu2O in situ prepared by the present invention has more excellent performance:
[0033] In CO2-saturated 0.1 M KOH solution, the total current ranged from -50 to -300 mA cm -2 In the range of -250 mA cm-1, the in-situ Cu2O-loaded nitrogen-rich carbon material prepared in Example 1 as a catalyst can effectively inhibit the hydrogen evolution reaction at high applied current and show high selectivity for C2 products. -2When , the Faraday efficiency of C2 product reaches 67.43%.
[0034] This result indicates that Cu2O(111) can promote the activation of CO2 to generate CO* and the CC coupling process, thereby improving the catalyst's ability to reduce CO2 to C 2+ Activity and selectivity of the products.
[0035] The nitrogen-rich carbon material loaded with Cu2O in situ of the present invention has excellent catalytic performance, and its mechanism is:
[0036] Carbon materials have the advantages of large specific surface area, stable chemical properties and good conductivity, but due to sp 2 or sp 3 Hybridized carbon atoms are very stable and cannot activate CO2 molecules. The doping of nitrogen atoms can induce more electrons to enter the carbon matrix, thereby producing more active sites. At the same time, the morphology, size and crystal surface of Cu nanoparticles can be regulated, which plays an important role in contributing to catalytic activity and improving the performance of carbon dioxide reduction.
[0037] The present invention has the following beneficial effects:
[0038] 1. The nitrogen-rich carbon material with in-situ loading of Cu2O prepared by the present invention utilizes nitrogen-doped carbon material to load Cu2O. While increasing the specific surface area, nitrogen atom doping can induce more electrons to enter the carbon matrix, thereby generating more active sites, and at the same time stabilizing the existence form of Cu2O (111), CO2 activation to generate CO* and CC coupling process, thereby generating multi-carbon products.
[0039] 2. The present invention uses glucose as a reducing agent at the same time. In the hydrothermal reaction, the reducing property of glucose is used to stabilize the divalent copper ions in a lower oxidation state, which is beneficial to the CC coupling in the CO2 reduction reaction process and improves the activity and selectivity of the electrocatalytic CO2 to C2 products.
[0040] 3. The nitrogen-rich carbon material loaded with Cu2O in situ prepared by the present invention can realize the efficient conversion of CO2 to C2 products, and the Faraday efficiency is greater than 60% at a higher total current density, and has broad application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The following is a further description with reference to the accompanying drawings.
[0042] Figure 1 This is an EDS image of the nitrogen-rich carbon material loaded with Cu2O in situ obtained in Example 1 of the present invention;
[0043] Figure 2 This is a dark field transmission electron microscope image of the nitrogen-rich carbon material loaded with in-situ Cu2O obtained in Example 1 of the present invention;
[0044] Figure 3 XRD diagram of the nitrogen-rich carbon material loaded with Cu2O in situ obtained in Examples 1-3 of the present invention;
[0045] Figure 4 This is an XPS graph of the nitrogen-rich carbon material with in-situ Cu2O loading obtained in Example 1 of the present invention;
[0046] Figure 5 Graph showing the Faraday efficiency of various products generated by the CO2 electroreduction of the nitrogen-rich carbon material with in-situ Cu2O loading prepared in Example 1 of the present invention at different reduction currents. DETAILED DESCRIPTION
[0047] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:
[0048] In the embodiments of the present invention, unless otherwise defined, all professional terms used hereinafter have the same meanings as those generally understood by those skilled in the art.
[0049] Unless otherwise specified, various reagents and raw materials used in the present invention can be purchased from the market.
[0050] Example 1
[0051] Step 1: Preparation of monovalent copper ion-doped gelatin precursor
[0052] Accurately weigh 1.5g of alkaline cowhide gelatin and 0.5g of anhydrous glucose. Add 8g of deionized water, swell at room temperature for 15min, and then place in a 60℃ water bath and stir to fully dissolve. Then add 0.31gCu(CH3COO)2·H2O to the above solution and stir for 50min. Put the above mixed solution into a hydrothermal kettle and react at 150℃ for 1h to obtain a monovalent copper gelatin solution. Put the monovalent copper gelatin solution into a refrigerator and freeze at -60℃ for 5h to obtain a monovalent copper gelatin frozen solid. Then put the monovalent copper gelatin frozen solid into a freeze dryer and place at -55℃ for 22h. After drying, a monovalent copper gelatin precursor is obtained.
[0053] Step 2: Preparation of nitrogen-rich carbon material loaded with Cu2O in situ
[0054] The monovalent copper gelatin precursor was placed in a muffle furnace and heated to 250°C at a heating rate of 10°C / min and kept warm for 1 hour. It was then taken out and placed in a tubular furnace and, under the protection of a N2 atmosphere, heated to 300°C at a heating rate of 10°C / min, and then heated to 900°C at a heating rate of 8°C / min, with a carbonization time of 1 hour.
[0055] The nitrogen-rich carbon material loaded with Cu2O in situ prepared in Example 1 can effectively inhibit the hydrogen evolution reaction under high applied current and show high selectivity for C2 products. -2 When , the Faradaic efficiency of C2 product reaches 67.43%.
[0056] Example 2
[0057] Step 1: Preparation of monovalent copper ion-doped gelatin precursor
[0058] Accurately weigh 1g of gelatin and 0.1g of anhydrous glucose from alkaline cowhide. Add 8.9g of deionized water, swell at room temperature for 30min, and then place in a 50℃ water bath and stir to fully dissolve. Then add 0.1gCu(CH3COO)2·H2O to the above solution and stir for 40min. Put the above mixed solution into a hydrothermal kettle and react at 100℃ for 1h to obtain a monovalent copper gelatin solution. Put the monovalent copper gelatin solution into a refrigerator and freeze it at -80℃ for 3h. After freezing, a monovalent copper gelatin frozen solid is obtained. Then, the monovalent copper gelatin frozen solid is placed in a freeze dryer and placed at -60℃ for 20h. After drying, a monovalent copper gelatin precursor is obtained.
[0059] Step 2: Preparation of nitrogen-rich carbon material loaded with Cu2O in situ
[0060] The monovalent copper gelatin precursor was placed in a muffle furnace and heated to 200°C at a heating rate of 1°C / min and kept warm for 3 hours. It was then taken out and placed in a tubular furnace and, under the protection of a N2 atmosphere, heated to 300°C at a heating rate of 10°C / min, and then heated to 1000°C at a heating rate of 8°C / min, with a carbonization time of 2 hours.
[0061] The nitrogen-rich carbon material loaded with Cu2O in situ prepared in Example 1 can effectively inhibit the hydrogen evolution reaction under high applied current and show high selectivity for C2 products. -2 When , the Faradaic efficiency of C2 product reaches 64.12%.
[0062] Example 3
[0063] Step 1: Preparation of monovalent copper ion-doped gelatin precursor
[0064] Accurately weigh 2g of alkaline cowhide gelatin and 1g of anhydrous glucose. Add 7g of deionized water, swell at room temperature for 20min, and then place in a 40℃ water bath and stir to fully dissolve. Then add 0.53gCu(CH3COO)2·H2O to the above solution and stir for 60min. Put the above mixed solution into a hydrothermal kettle and react at 200℃ for 1h to obtain a monovalent copper gelatin solution. Put the monovalent copper gelatin solution into a refrigerator and freeze it at -0℃ for 8h. After freezing, a monovalent copper gelatin frozen solid is obtained. Then the monovalent copper gelatin frozen solid is placed in a freeze dryer and placed at -50℃ for 24h. After drying in an air dryer, a monovalent copper gelatin precursor is obtained.
[0065] Step 2: Preparation of nitrogen-rich carbon material loaded with Cu2O in situ
[0066] The above-mentioned monovalent copper gelatin precursor was placed in a muffle furnace and heated to 250°C at a heating rate of 6°C / min and kept warm for 2 hours. It was then taken out and placed in a tubular furnace and, under the protection of a N2 atmosphere, heated to 300°C at a heating rate of 10°C / min, and then heated to 500°C at a heating rate of 3°C / min, and the carbonization time was 1 hour.
[0067] The nitrogen-rich carbon material loaded with Cu2O in situ prepared in Example 1 can effectively inhibit the hydrogen evolution reaction under high applied current and show high selectivity for C2 products. -2 When , the Faradaic efficiency of C2 product reaches 65.97%.
[0068] Comparative Example 1
[0069] Accurately weigh 1.5g of gelatin from alkaline cowhide and 0.5g of anhydrous glucose. Add 8g of deionized water, swell at room temperature for 15min, and then stir in a 60℃ water bath to fully dissolve. Put the above gelatin solution into a refrigerator and freeze it at -60℃ for 5h. After freezing, obtain a gelatin frozen solid. Then put the gelatin frozen solid into a freeze dryer and place it at -55℃ for 22h. After drying, obtain a gelatin precursor.
[0070] The above gelatin precursor was placed in a muffle furnace and heated to 250°C at a heating rate of 10°C / min and kept warm for 1 hour. It was then taken out and placed in a tubular furnace and, under the protection of a N2 atmosphere, heated to 300°C at a heating rate of 10°C / min, and then heated to 900°C at a heating rate of 8°C / min, with a carbonization time of 1 hour.
[0071] The pure nitrogen-rich carbon material prepared in Comparative Example 1 was used as a catalyst, and the selectivity for C2 products was low. -2 When the C2 product Faradaic efficiency is less than 5.35%.
[0072] Catalyst performance evaluation
[0073] All electrochemical measurements in this study were performed using an electrochemical station from Auto Lab in a typical three-electrode system. A custom-made flow-type electrolytic cell was used, with a conventional three-electrode system consisting of a gas diffusion electrode (YLS-30T) with a catalyst coating, an Ag / AgCl reference electrode (3.5 M KCl), and a Pt mesh counter electrode. An anion exchange membrane (FAA-3-PK-130) was used to separate the two compartments. The electrolyte at the cathode was a 0.1 M KOH solution.
[0074] Preparation of carbon paper working electrode:
[0075] 10 mg of the in-situ Cu2O-loaded nitrogen-rich carbon material was mixed with 470 μL of ethanol, 475 μL of deionized water, and 50 μL of Nafion solution (5 wt %, Sigma-Aldrich), and then sonicated for 1 h to form a uniform catalyst ink.
[0076] 200 μL of the obtained catalyst ink was added dropwise twice to a gas diffusion electrode (1×2 cm 2 ) and dried directly at 50°C for 1 h.
[0077] The preparation of the comparative carbon paper working electrode was performed by simply changing the nitrogen-rich carbon material with 10 mg of in-situ Cu2O loaded to the pure nitrogen-rich carbon material prepared in Comparative Example 1.
[0078] Analysis of the experimental results obtained:
[0079] The nitrogen-rich carbon material loaded with Cu2O in situ prepared by Examples 1-3 can effectively inhibit the hydrogen evolution reaction under high applied current and show high selectivity for C2. total -250mA cm -2 When the C2 Faradaic efficiency is greater than 60%.
[0080] This result indicates that nitrogen-rich carbon materials loaded with Cu2O in situ can promote the activation of CO2 to generate CO* and the CC coupling process, thereby improving the activity and selectivity of the catalyst in reducing CO2 to C2 products.
[0081] The various properties of the in-situ Cu2O-loaded nitrogen-rich carbon material prepared by the present invention are further described by the accompanying drawings:
[0082] Figure 1 This is an EDS image of the nitrogen-rich carbon material with in-situ Cu2O loading obtained in Example 1 of the present invention; copper particles are evenly added to the nitrogen-rich carbon material, and each element is evenly distributed. Copper and nitrogen are evenly dispersed in the carbon material, indicating that nitrogen is successfully doped into the carbon substrate.
[0083] Figure 2 This is a dark field transmission electron microscope image of the nitrogen-rich carbon material loaded with Cu2O in situ obtained in Example 1 of the present invention; Figure 2 It can be seen that Cu2O nanoparticles are in situ grown on the surface of the prepared nitrogen-rich carbon material, and the lattice spacing is 0.246nm, which corresponds to the (111) crystal plane of Cu2O.
[0084] Figure 3 XRD diagram of the nitrogen-rich carbon material loaded with Cu2O in situ obtained in Examples 1-3 of the present invention; Figure 3 It can be seen that 27.4° corresponds to the interlayer stacking (002) crystal plane of the conjugated aromatic rings of carbon. After in-situ loading of Cu2O, the structure of the carbon material has hardly changed. The peaks at 42.6°, 51.2° and 74.1° belong to the (111), (100) and (110) crystal planes of Cu2O, respectively, indicating the formation of Cu2O nanocrystals.
[0085] Figure 4 This is the XPS graph of the nitrogen-rich carbon material loaded with Cu2O in situ obtained in Example 1 of the present invention. Figure 4 It can be seen that there are two strong peaks at 932.3 and 952.3 eV, and the spin-orbit splitting is 20.0 eV, corresponding to Cu 0 / Cu + Cu2ρ 3 / 2 and Cu2p 1 / 2 Characteristic peaks indicate that Cu 2+ of restoration. Figure 4 b The Auger electron spectrum of Cu LMM shows a small peak at 566.8 eV and a strong peak at 571.2 eV, revealing that Cu in the nitrogen-rich carbon material loaded with Cu2O in situ 0 and Cu + This further proves that there is a large amount of Cu2O in the nitrogen-rich carbon material.
[0086] Figure 5 The Faraday efficiency diagram of the CO2 electroreduction of the nitrogen-rich carbon material loaded with Cu2O in situ prepared in Example 1 of the present invention to generate various products under different reduction currents. Figure 5 It can be seen that in a CO2-saturated 0.1 M KOH solution, the applied reduction current ranged from -100 to -350 mA cm -2 In the range of -250 mA cm-1, the nitrogen-rich carbon material loaded with Cu2O in situ prepared in Example 1 can effectively inhibit the hydrogen evolution reaction under high applied current and show high selectivity for C2 products. -2 When , the Faradaic efficiency of C2 product reaches 67.43%.
[0087] This result indicates that the nitrogen-rich carbon material loaded with Cu2O in situ promotes the activation of CO2 to generate CO* and the CC coupling process, thereby improving the activity and selectivity of the catalyst in reducing CO2 to C2 products.
[0088] The nitrogen-rich carbon material loaded with Cu2O in situ prepared by the present invention uses nitrogen-doped carbon to load Cu2O in situ. While increasing the electrochemical active area, N doping can make Cu2O stable in a lower oxidation state. The nitrogen-rich carbon material loaded with Cu2O in situ promotes the activation of CO2 to generate CO* and CC coupling process. The nitrogen-rich carbon material loaded with Cu2O in situ prepared by the present invention can achieve efficient conversion of CO2 to C2 products, and the Faraday efficiency is greater than 60% at a higher total current density, and has broad application value.
[0089] The present invention is described above by way of example in conjunction with the accompanying drawings. It is obvious that the implementation of the present invention is not limited to the above-mentioned method. As long as various improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A method for preparing a nitrogen-rich carbon material loaded with Cu2O in situ, characterized in that it comprises the following steps: Step 1: Preparation of monovalent copper ion-doped gelatin precursor 1.1 Add gelatin and anhydrous glucose into a solvent to swell and dissolve, thereby obtaining a solution of gelatin and glucose mixture; 1.2 Then, add the copper salt to the mixed solution of gelatin and glucose obtained in step 1.1, and stir to obtain a mixture; 1.3 The mixture obtained in step 1.2 is placed in a hydrothermal reactor for hydrothermal reaction to obtain a monovalent copper ion-doped gelatin solution; 1.4 The monovalent copper ion-doped gelatin solution obtained in step 1.3 is placed in a refrigerator and frozen to obtain a monovalent copper ion-doped gelatin frozen solid; 1.5 The monovalent copper ion-doped gelatin frozen solid obtained in step 1.4 is placed in a freeze dryer, and after drying, a monovalent copper ion-doped gelatin precursor is obtained; Step 2: Preparation of in-situ Cu2O-loaded nitrogen-rich carbon materials for CO2 reduction 2.1 The monovalent copper ion-doped gelatin precursor obtained in step 1 is placed in a muffle furnace for cross-linking reaction to obtain cross-linked monovalent copper ion-doped gelatin; 2.2 The cross-linked monovalent copper ion-doped gelatin obtained in step 2.1 is carbonized under N2 or Ar conditions to obtain a nitrogen-rich carbon material in situ loaded with Cu2O for CO2 reduction.
2. The method for preparing a nitrogen-rich carbon material loaded with Cu2O in situ according to claim 1, characterized in that: In the step 1.1, the mass fraction of gelatin is 10%-20%, the mass fraction of anhydrous glucose is 1%-10%, the solvent is deionized water, the swelling temperature is 15-40°C, and the dissolution temperature is 40-60°C; In the step 1.2, after the copper metal salt is added to the mixed solution of gelatin and glucose, the mass fraction of the copper metal salt is 1-5%; and the stirring time is 40-60 minutes.
3. The method for preparing a nitrogen-rich carbon material loaded with Cu2O in situ according to claim 1, characterized in that: In the step 1.3, the reaction temperature of the mixture in the hydrothermal reactor is 100-200° C. and the reaction time is 1-2 h; In the step 1.4, the freezing temperature of the refrigerator is -80-0°C, and the freezing time is 3-8h; In the step 1.5, the freeze-drying temperature in the freeze-drying method is -60 to -50°C, and the freeze-drying time is 20 to 24 hours.
4. The method for preparing a nitrogen-rich carbon material loaded with Cu2O in situ according to claim 1, characterized in that: In the step 2.1, the cross-linking temperature in the cross-linking method is 200-300°C, the cross-linking time is 1-3h, and the heating rate is 1-10°C / min.
5. The method for preparing a nitrogen-rich carbon material loaded with Cu2O in situ according to claim 1, characterized in that: In the step 2.2, the carbonization temperature in the carbonization method is 500-1000° C., and the carbonization time is 1-2 hours.
6. A nitrogen-rich carbon material loaded with Cu2O in situ, characterized in that: The invention is prepared according to the preparation method described in any one of claims 1 to 5.
7. Use of the nitrogen-rich carbon material in situ loaded with Cu2O according to claim 6 in the electro-reduction of CO2, characterized in that: The electrode material was prepared by in-situ loaded Cu2O nitrogen-rich carbon material for electrocatalytic CO2 reduction.
8. The use of the nitrogen-rich carbon material loaded with in-situ Cu2O in the electro-reduction of CO2 according to claim 7, characterized in that: The specific operation includes the following steps: The in-situ Cu2O-loaded nitrogen-rich carbon material is dispersed in a mixed solution of ethanol and naphthol film ethanol dispersion, and drop-coated on carbon paper as a working electrode, an Ag / AgCl electrode as a reference electrode, and a platinum sheet as a counter electrode; the cathode electrolyte is a CO2-saturated KOH solution.
9. The use of the nitrogen-rich carbon material loaded with Cu2O in situ according to claim 8 in the electro-reduction of CO2, characterized in that: The electrolyte of the cathode is one of 0.1-1M KOH solution, NaOH solution and KHCO3 solution.
10. The use of the nitrogen-rich carbon material loaded with in-situ Cu2O in the electro-reduction of CO2 according to claim 8, characterized in that: The loading amount of the in-situ Cu2O-loaded nitrogen-rich carbon material is 0.5-2 mg / cm 2 .
Citation Information
Patent Citations
Preparation method of nitrogen-doped activated carbon-supported Cu catalyst and application thereof in catalyzing furfural hydrogenation
CN109261182A
Cu2O / N-C oxygen reduction catalyst and preparation and application thereof
CN112018398A
Catalyst for preparing ethylene through CO2 electroreduction as well as preparation method and application of catalyst
CN115418666A
Carbon dioxide electro-catalytic material for optimizing interface through reducing atmosphere as well as preparation method and application of carbon dioxide electro-catalytic material
CN115786960A
Copper-based catalyst rich in Cu0 / Cu < + > interfacial active sites as well as preparation method and application of copper-based catalyst
CN116288421A